2005
DOI: 10.1002/jhet.5570420506
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and chemical reactivity of 3‐oxo‐2‐arylhydrazono‐propanenitriles

Abstract: 2-Formyl-2-arylhydrazonoethanenitriles 6b-d where prepared via reacting enaminonitrile 2b,c with aromatic diazonium salts. These reacted with phenylhydrazine to yield bis hydrazones that were converted to arylazopyrazoles via a novel Vilsmeier-Haack reaction type. Reaction of 6c with hydroxylamine afforded oxime that could be successfully cyclised into arylazoisoxazole. Reaction of 6c with hydrazine hydrate to yield arylazoaminopyrazole that proved to be excellent precursors for synthesis functional substitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 23 publications
(19 reference statements)
1
31
1
Order By: Relevance
“…Enaminones 2a-g coupled with diazotized methyl anthranilate 3a or diazotized anthranilonitrile 3b in the presence of ethanolic sodium acetate to yield the corresponding aryl hydrazone coupling products 6 a-h [17,27] (Scheme 2). When N,N-dimethylamino-3-buten-2-one (2a) and 3-N,N-dimethylamino-1-(4-chloro phenyl)-2-propen-1-one (2g) were treated with excess diazotized anthranilonitrile 3b the bisazo compounds 7a and 7b was formed in a Japp-Klingmann type reaction which proceed via intermediate formation of 6a,b [28] We also report herein on the reactivity of 6a-h towards a variety of nitrogen and carbon nucleophiles in the absence of solvent under irradiation (μω) in a domestic microwave oven. The yields of products obtained under the microwave heating technique μω and the time taken to complete the reactions are compared with those obtained by conventional heating (Δ) in Table 2 (see Experimental).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enaminones 2a-g coupled with diazotized methyl anthranilate 3a or diazotized anthranilonitrile 3b in the presence of ethanolic sodium acetate to yield the corresponding aryl hydrazone coupling products 6 a-h [17,27] (Scheme 2). When N,N-dimethylamino-3-buten-2-one (2a) and 3-N,N-dimethylamino-1-(4-chloro phenyl)-2-propen-1-one (2g) were treated with excess diazotized anthranilonitrile 3b the bisazo compounds 7a and 7b was formed in a Japp-Klingmann type reaction which proceed via intermediate formation of 6a,b [28] We also report herein on the reactivity of 6a-h towards a variety of nitrogen and carbon nucleophiles in the absence of solvent under irradiation (μω) in a domestic microwave oven. The yields of products obtained under the microwave heating technique μω and the time taken to complete the reactions are compared with those obtained by conventional heating (Δ) in Table 2 (see Experimental).…”
Section: Resultsmentioning
confidence: 99%
“…It is proposed that when Ac 2 O is present the glycine is acetylated to N-acetylglycine and then this compound cyclizes to form 2-methyloxazol-5-one (15a) and the latter in turn condensed with the arylhydrazone derivatives 6a,b,d-f,h to form the intermediate 16 which cannot be isolated, but then rearranges to form pyridazinone derivatives 17a-f. Similarly hippuric acid cyclized in the presence of Ac 2 O to give 5-phenyloxazol-5-one (15a) and then this compound condensed with arylhydrazone derivative 6a to gave pyridazinone derivative 17g [28,29]. Recently Elnagdi et al [10,30,31] have described a synthesis of pyridazine-5,6-dicarbonates 22a,b via reaction of 6b,e with dimethyl acetylenedicarboxylate in the presence of diphenylphosphine.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the behaviour of 2 the nitrile 9, recently obtained in our laboratories via reacting 11 with benzenediazonium chloride [3], reacted with hydroxylamine hydrochloride in DMF solution to yield the arylazo-1,2,3-triazoleamime 10. In addition, when compound 11 reacted with hydroxylamine hydrochloride, the amidoxime 12 was produced and then cyclized in Ac 2 O into acetylaminoisoxazole 13 (Scheme 2).…”
Section: Resultsmentioning
confidence: 76%
“…Arylhydrazononitriles are readily obtainable materials [1][2][3] and their chemistry has been extensively investigated in our laboratories [4][5][6]. The utility of some of the arylhydrazononitriles by several other authors in published [7] and patent [8,9] literature prompted us to explore further interesting synthetic potentials of such compounds as precursors for heteroaromatic amines that could be utilized as intermediates in dye and pharmaceutical industries [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Elnagdi et al (2,7,30) have reported that refluxing 2-arylhydrazononitriles with functionally substituted alkyl halides afforded 4-aminopyrazole derivatives. Now, compound 4 was next reacted with chloroacetonitrile, under conventional heating, Mw irradiation, and sonication, to afford the 4-aminopyrazoles 13, via the acyclic non-isolable intermediate 12 (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%